MEWFM 2023
DOI: 10.5742/mewfm.2023.95256020
|View full text |Cite
|
Sign up to set email alerts
|

Screening the risk of eating disorders among adolescents in primary care centres in Makkah, Saudi Arabia

Abstract: Background: Obesity significantly affects daily activities and contributes to countless diseases and comorbidities that can drastically alter an individual’s life. This study aims to measure the awareness of the indications and complications of sleeve gastrectomy in Riyadh, Saudi Arabia. Methods: This study was cross-sectional, and participants completed an online self-administered questionnaire on sleeve gastrectomy in Riyadh through Google Forms. Data were entered into Microsoft Excel 2013 and statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Using SCOFF screening measurement, many studies reported high level of risk of eating disorders especially among adolescents in Makkah city. A study in primary health care settings found more than 50% of the respondents had the risk of eating disorders(Hariri, 2023). Another study in secondary schools revealed 46% of adolescents had greater risk of eating disorders.…”
mentioning
confidence: 99%
“…Using SCOFF screening measurement, many studies reported high level of risk of eating disorders especially among adolescents in Makkah city. A study in primary health care settings found more than 50% of the respondents had the risk of eating disorders(Hariri, 2023). Another study in secondary schools revealed 46% of adolescents had greater risk of eating disorders.…”
mentioning
confidence: 99%